Mechanisms of obesity in children and adults with phenylketonuria on contemporary treatment. (December 2021) - Alghamdi, Nouf; Alfheeaid, Hani; Cochrane, Barbara; Adam, Sarah; Galloway, Peter; Cozens, Alison; Preston, Tom; Malkova, Dalia; Gerasimidis, Konstantinos
Summary: Background & aims: Obesity prevalence in people with phenylketonuria (PKU) is comparable to that of the general population but the underlying aetiology remains unknown. To assess body composition, dietary intake, moderate physical activity duration (MPAD) and energy expenditure (MPAEE), resting metabolic rate (RMR), diet-induced thermogenesis (DIT), fasting and postprandial fat (FOx) and carbohydrate oxidation (CHOOx), in PKU people and healthy Controls. Methods: Participants were PKU people (n = 16) and healthy controls (n = 15). Body composition was measured with stable isotopes using deuterium as tracer, dietary intake from 4-day food diaries, MPAD and MPAEE from 7-day activity counts measured by triaxial accelerometers, calibrated against individual rates of oxygen consumption and carbon dioxide production, RMR, DIT, FOx and CHOOx by indirect calorimetry. Results: Body composition, DIT, FOx, CHOOx and RMR did not differ between the PKU and the Control groups. MPAD (PKU, 73 ± 26 min/week; Control, 152 ± 43 min/week) and MPAEE (PKU, 404 ± 127 kcal/week; Control, 741 ± 153 kcal/week) were lower (P < 0.05) in the PKU than the Control group. Raised phenylalanine levels were inversely related with MPAD and MPAEE. Energy intake and energy provided by protein did not differ between the groups, while energy proportion obtained from carbohydrate was higher (PKU, 60 ± 2%; Control, 51 ± 2%; P < 0.05) and from fat lower (PKU, 24 ± 2%; Control, 35 ± 3%; P < 0.05) in the PKU than in the Control group. Conclusion: People with PKU spent less time and expend less energy in moderate physical activity and have a higher intake of energy from CHO which may be involved in the underlying mechanisms of obesity in PKU.